Placental Transfusion and Cardiovascular Instability in the Preterm Infant - Straňák, Zbynĕk; Feyereislová, Simona; Korček, Peter; Dempsey, Eugene (Frontiers in Pediatrics, 2018)
Postnatal adaptation in preterm newborn comprises complex physiological processes that involve significant changes in the circulatory and respiratory system. Increasing haemoglobin level and blood volume following placental transfusion may be of importance in enhancing arterial oxygen content, increasing cardiac output and improving oxygen delivery. The European consensus on resuscitation of preterm infants recommends delayed cord clamping (DCC) for at least 60 seconds to promote placenta-fetal transfusion in uncompromised neonates. Recently published meta-analyses suggest that DCC is associated with fewer infants requiring transfusions for anaemia, a lower incidence of intraventricular haemorrhage (IVH) and lower risk for necrotizing enterocolitis. Umbilical cord milking (UCM) has the potential to avoid some disadvantages associated with DCC including the increased risk of hypothermia or delay in commencing manual ventilation. UCM represents an active form of blood transfer from placenta to neonate and may have some advantages over DCC. Moreover, both methods are associated with improvement in haemodynamic parameters and blood pressure within first hours after delivery compared to immediate cord clamping. Placental transfusion appears to be beneficial for the preterm uncompromised infant. Further studies are needed to evaluate simultaneous placental transfusion with resuscitation of deteriorating neonates. It would be of great interest for future research to investigate advantages of this approach further and to assess its impact on neonatal outcomes, particularly in extremely preterm infants.